Bacillus radicibacter sp. nov., a new bacterium isolated from root nodule of Oxytropis ochrocephala Bunge. (27th July 2015) - Wei, Xiu Li; Lin, Yan Bing; Xu, Lin; Han, Meng Sha; Dong, Dan Hong; Chen, Wei Min; Wang, Li; Wei, Ge Hong
<x xml:space="preserve">Abstract</x> A Gram‐positive, facultative anaerobic, rod‐shaped, and endospore‐forming strain, designated 53‐2T was isolated from the root nodule of Oxytropis ochrocephala Bunge growing on Qilian mountain, China. The strain can grow at pH 7.0–8.0, 10–50 °C and tolerate up to 11% NaCl. Optimal growth occurred at pH 7.2 and 37 °C. The result of BLASTn search based on 16S rRNA gene sequence revealed that strain 53‐2T, being closest related to Bacillus acidicola 105‐2T, possessed remote similarity (less than 95.64%) to the species within genus Bacillus. The DNA G + C content was 37.8%. Chemotaxonomic data (major quinone is MK‐7; major polar lipids are diphosphatidylglycerol, phosphatidylglycerol, unknown phospholipid, and aminoglycophospholipid; fatty acids are anteiso‐C15: 0, iso‐C15:0 and anteiso‐C17: 0) supported the affiliation of the isolate to the genus Bacillus. On the basis of physiological, phylogenetic, and biochemical properties, strain 53‐2T represents a novel species within genus Bacillus, for which the name Bacillus radicibacter is proposed. The type strain is 53‐2T (=DSM27302T=ACCC06115T=CCNWQLS5T).